Flor de muertos - Vinik, Danny (Sonication Films : Brink Films, 2011)
A celebratory journey into the rich borderlands culture between Tucson, Arizona and the towns of Nogales, Arizona and Mexico. Director Danny Vinik evokes the power and beauty of the Sonoran Desert and its people in this poetic exploration of life and death along the US/Mexico border. Features a stunning performance by acclaimed Americana band Calexico at Tucson's historic Rialto Theatre.